Does albumin predict the risk of mortality in patients with cardiogenic shock? - Schupp, Tobias; Behnes, Michael; Rusnak, Jonas; Ruka, Marinela; Dudda, Jonas; Forner, Jan; Egner-Walter, Sascha; Barre, Max; Abumayyaleh, Mohammad S. A.; Bertsch, Thomas; Müller, Julian; Akın, Ibrahim (International journal of molecular sciences, 2023)
This study investigates the prognostic impact of albumin levels in patients with cardiogenic shock (CS). Intensive care unit (ICU) related mortality in CS patients remains unacceptably high despite improvement concerning the treatment of CS patients. Limited data regarding the prognostic value of albumin in patients with CS is available. All consecutive patients with CS from 2019 to 2021 were included at one institution. Laboratory values were retrieved from the day of disease onset (day 1) and days 2, 3, 4, and 8 thereafter. The prognostic impact of albumin was tested for 30-day all-cause mortality. Moreover, the prognostic performance of albumin decline during ICU treatment was examined. Statistical analyses included univariable t-test, Spearman’s correlation, Kaplan-Meier analyses, multivariable mixed analysis of variance (ANOVA), C-Statistics, and Cox proportional regression analyses. In total, 230 CS patients were included, with an overall all-cause mortality at 30 days of 54%. The median albumin on day 1 was 30.0 g/L. Albumin on day 1 was able to discriminate between 30-day survivors and non-survivors (area under the curve (AUC) 0.607; 0.535-0.680; p = 0.005). CS patients with albumin < 30.0 g/L were associated with an increased risk of 30-day all-cause mortality (63% vs. 46%; log-rank p = 0.016; HR = 1.517; 95% CI 1.063-2.164; p = 0.021), which was demonstrated even after multivariable adjustment. Moreover, a decrease of albumin levels by ≥20% from day 1 to day 3 was accompanied by a higher risk of 30-days all-cause mortality (56% vs. 39%; log-rank p = 0.036; HR = 1.645; 95% CI 1.014-2.669; p = 0.044). Especially when combined with lactate, creatinine, and cardiac troponin I, reliable discrimination of 30-day all-cause mortality was observed, including albumin in CS risk stratification models (AUC = 0.745; 95% CI 0.677-0.814; p = 0.001). In conclusion, low baseline albumin levels as well as a decay of albumin levels during the course of ICU treatment, deteriorate prognostic outcomes in CS patients. The additional assessment of albumin levels may further improve risk stratification in CS patients.
Gesehen am 14.06.2023